HubunganPengetahuan Mahasiswa Fakultas Kedokteran Universitas Sebelas Maret Mengenai Resusitasi Jantung Paru dengan Kepercayaan Diri Mahasiswa dalam Melakukan Tindakan Penyelamatan - Kirana, Tara Ken Wita; Wicaksono, Bagus; Hanim, Diffah (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background:Cardio Pulmonary Resusitation (CPR) is an emergency procedure, performed in an effort to restore spontaneous blood circulation and breathing in cardiac arrest and respiratory arrest. Untill now, CPR is one of the most important procedure in first aid of heart attack, also in respiratory arrest and cardiac arrest due to trauma. CPR need to be performed in a fast and effective way, therefore knowledge of CPR and confidence in perform CPR is needed. This research aims to analyze the relationship beetwen medical studentâs of Sebelas Maret University knowledge in CPR with studentâs confidence in performing a rescue. Methods:The research was an analytical survey with cross sectional approach implemented in May-June 2013 in Faculty of Medicine Sebelas Maret University. The number of samples in this study was 129 students with the inclusion and exclusion criteria and the samples sampling by simple random sampling. Dependent variable was studentâs confidence in performing a rescue and independent variable was studentâs knowledge in CPR. This research was conducted with questionnaires by samples and then the data were analyzed by Pearson Correlation. Results:This research showed significant relationship beetwen student knowledge in CPR and students confidence in performing a rescue (p = 0.000).This study showed that 93 students (72.09%) didnât know the exact location of chest compression, 21 students (16.27%) didnât know the right recovery position for patient, 129 students (100%) wanted to gain more training and knowledge in CPR, 42 respondents (32.55%) acknowledged that they were still not able to perform CPR effectively, and 40 students (31%) stated that they were not able to perform breathing support in an accurate and effective way. Conclusions:The relationship beetwen medical studentâs of Sebelas Maret University knowledge in cardio pulmonary resusitation with studentâs confidence in performing a rescue were significant. Keywords:Cardio pulmonary resusitation, confidence, rescue